Development and review of the voluntary phase of a national BVD eradication programme in Ireland. (18th January 2014) - Graham, D. A.; Lynch, M.; Coughlan, S.; Doherty, M. L.; O'Neill, R.; Sammin, D.; O'Flaherty, J.
Abstract : The voluntary phase of an industry‐led national Bovine Viral Diarrhoea (BVD) eradication programme began in Ireland on January 1, 2012 with the goal of progressing to a compulsory programme in 2013. The development and implementation of the programme in 2012 was informed by a review of current and prior eradication programmes elsewhere in Europe and extensive stakeholder consultation. The programme was based on tissue tag testing of newborn calves in participating herds, with the status of the mothers of calves with positive or inconclusive results requiring clarification. Participating herd owners were required to comply with a series of guidelines, including not selling cattle suspected of being persistently infected. For herds compliant with the guidelines, the results from 2012 counted as one of three years of tag testing anticipated in the compulsory phase of the programme. Testing was carried out in laboratories designated for this purpose by the cross‐industry BVD Implementation Group that oversees the programme. Results were reported to a central database managed by the Irish Cattle Breeding Federation, and the majority of results were reported to farmers' mobile telephones by SMS message. A detailed review of the programme was conducted, encompassing the period between January 1, 2012 and July 15, 2012, based on results from approximately 500, 000 calves. This paper describes the establishment and structure of the programme, and the outcomes of the review, including findings at herd and animal level.